Best Answer

Change the order to make it more obvious:

3a - a + 2b + 4b

2a + 6b or 2 (a + 3b).

Q: How do you simplify 3a plus 2b - a plus 4b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

c-2b

The simplified answer is: 4c+2b

Numerically, if the question looks like this:--(3a + 7b) - 8a - 4b + 2Then the answer is this:--3a - 7b - 8a - 4b + 2= -11a -11b + 2

The first equation factors to (3x + 2)(3x + 4) The second equation factors to (3a + 2b)(3a + 4b)

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

Related questions

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b

2a + 4b

It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus

It is: 4b+16 simplified

Clearly, there are some signs missing. So let's try the four possibilities for the second terms: 1. + and + 3a + 4b = 7a + 4b Subtract 4b from each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 2. + and - 3a + 4b = 7a - 4b Subtract 4b from each side: 3a = 7a - 8b Subtract 7a from each side: -4a = -8b or 4a = 8b Answer: a = 2b 3. - and - 3a - 4b = 7a - 4b Add 4b to each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 4. - and + 3a - 4b = 7a + 4b Add 4b to each side: 3a = 7a + 8b Subtract 7a from each side: -4a = 8b or 4a = -8b Answer: a = -2b Can't do better than that with the information available.

7(a-2b)-6(a-4b) 7a - 14b - 6a - 24b 7a - 6a - 14b - 24b a - 38b

c-2b

The simplified answer is: 4c+2b

-2b+8-4b = -5-11b+7 -2b-4b+11b = -5+7-8 5b = -6 b = -6/5

1a+3b 2a+4b=3a +7b

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5